Spatial Fairness Index : Measuring How Projects Reach Their Intended Beneficiaries - Cesar, Sylvia (World Bank, Washington, DC, 2020)
Portfolio Footprints compare sub-national data on World Bank portfolio allocations with indicators of need, including poverty. Such analyses allow a better understanding of the spatial distribution of Bank investments and whether these investments are reaching their intended beneficiaries. In this note we present the Spatial Fairness Index (SFI), which provides a summary indicator of the inequality in projects’ investments with respect to a fair allocation benchmark. We present an application of this Index in the context of the World Bank portfolio in Bangladesh. We highlight some of the SFI’s main uses: to compare across sectors, projects and time, as well as to inform project design.